Supramolecular gel composites reinforced by using halloysite nanotubes loading with in-situ formed Fe3O4 nanoparticles and used for dye adsorption. (18th January 2016) - Zeng, Xiaoping; Sun, Zhonghui; Wang, Hong; Wang, Qin; Yang, Yajiang
Abstract: An inherent disadvantage of supramolecular gels is the lack of mechanical strength. In this work, we made an attempt to improve their mechanical strength through the adding hydrophobically modified halloysite nanotubes (HNTs) with in-situ formed Fe3 O4 nanoparticles. Briefly, the magnetic supramolecular gel composites were prepared through adding 2 wt% benzyl sorbitol derivatives as the gelators into the solvents containing magnetic HNTs. It was found that the compressive strength of the reinforced supramolecular gel composites was remarkably increased from 19 kPa to 28 kPa by adding only 4 wt% of magnetic HNTs. The resultant magnetic supramolecular gel composites possess formability due to their sufficient mechanical strength and exhibit excellent properties for dye adsorption. Significantly, such magnetic supramolecular gel composites can be easily separated from the dye solutions by using an external magnet.